Adobe InDesign CS4 : Classroom in a book (San Jose, California : Adobe Systems Incorpoprated, 2009)
This book is part of the official training series for Adobe graphics and publishing software from Adobe Systems, Inc.
1. Introducing the workspace -- 2. Getting to know indesign -- 3. Setting up a document and working with pages -- 4. Working with frames -- 5. Importing and editing text -- 6. Working with typography -- 7. Working with color -- 8. Working with styles -- 9. Importing and modifying graphics -- 10. Creating tables -- 11. Working with transparency -- 12. Working with long documents -- 13. Output and exporting -- 14. Creating rich interactive documents
Includes index.
Keywords: ADOBE INDESIGN (ELECTRONIC SOURCE); DESKTOP PUBLISHING; EDUCATION